Association between dietary satisfaction and depression, anxiety and stress in obese and overweight patients during the coronavirus pandemic. (October 2021) - Moradi, Fatemeh; Heshmati, Javad; Daneshzad, Elnaz; Ahmadi, Ali; Jafari, Tina; Persad, Emma; Fazelian, Siavash
Summary: Background & aim: The coronavirus disease-2019 (COVID-19) pandemic is a global health threat. The aim of this study was to evaluate the association between D-Sat and depression, anxiety and stress in obese patients during the coronavirus pandemic. Methods: A cross-sectional study in 228 obese and overweight women on a weight loss diet was conducted through the use of two questionnaires. General characteristics, anthropometric indices, D-Sat and mental status were assessed in these patients. Results: The greatest weight loss (WL) and waist circumference (WC) change was associated with the highest tertile of the D-Sat score in the first four months of the coronavirus pandemic (P < 0.05). Participants with the highest tertile of all D-sat score compared to those with the lowest had an 84% decrease in odds of depression. The highest tertile was also associated with decreased odds of anxiety (OR: 0.32 95%CI: 0.14; 0.68) The adjusted odds of stress score were negatively associated to the highest tertile of the D-Sat score (OR: 0.09, 95%CI (0.03, 0.23). WL was inversely related to stress (P < 0.05). Participants with higher WL and WC reduction had fewer depressive symptoms (P < 0.05). Sleep time and family income were associated with obesity. Conclusions: D-Sat and positive personal and family dynamics can improve the mental status of obese and overweight patients during quarantine. Highlights: All seven subscales of the D-Sat questionnaire were significantly inversely related to participants' moods disorders. Dietary satisfaction was associated with improved mental health. Higher WL and WC reduction were associated with a significant reduction depressive symptoms.